Digits in a dish: An in vitro system to assess the molecular genetics of hand/foot development at single-cell resolution - Fuiten, Allison M.; Yoshimoto, Yuki; Shukunami, Chisa; Stadler, H. Scott (Frontiers in Cell and Developmental Biology, 2023)
In vitro models allow for the study of developmental processes outside of the embryo. To gain access to the cells mediating digit and joint development, we identified a unique property of undifferentiated mesenchyme isolated from the distal early autopod to autonomously re-assemble forming multiple autopod structures including: digits, interdigital tissues, joints, muscles and tendons. Single-cell transcriptomic analysis of these developing structures revealed distinct cell clusters that express canonical markers of distal limb development including: Col2a1, Col10a1, and Sp7 (phalanx formation), Thbs2 and Col1a1 (perichondrium), Gdf5, Wnt5a, and Jun (joint interzone), Aldh1a2 and Msx1 (interdigital tissues), Myod1 (muscle progenitors), Prg4 (articular perichondrium/articular cartilage), and Scx and Tnmd (tenocytes/tendons). Analysis of the gene expression patterns for these signature genes indicates that developmental timing and tissue-specific localization were also recapitulated in a manner similar to the initiation and maturation of the developing murine autopod. Finally, the in vitro digit system also recapitulates congenital malformations associated with genetic mutations as in vitro cultures of Hoxa13 mutant mesenchyme produced defects present in Hoxa13 mutant autopods including digit fusions, reduced phalangeal segment numbers, and poor mesenchymal condensation. These findings demonstrate the robustness of the in vitro digit system to recapitulate digit and joint development. As an in vitro model of murine digit and joint development, this innovative system will provide access to the developing limb tissues facilitating studies to discern how digit and articular joint formation is initiated and how undifferentiated mesenchyme is patterned to establish individual digit morphologies. The in vitro digit system also provides a platform to rapidly evaluate treatments aimed at stimulating the repair or regeneration of mammalian digits impacted by congenital malformation, injury, or disease.